A Comprehensive Review on Phytochemistry and Pharmacological Activities of Clinacanthus nutans (Burm.f.) Lindau. (4th July 2018) - Khoo, Leng Wei; Audrey Kow, Siew; Lee, Ming Tatt; Tan, Chin Ping; Shaari, Khozirah; Tham, Chau Ling; Abas, Faridah
Abstract : Clinacanthus nutans (Burm.f.) Lindau (Acanthaceae), commonly known as Sabah snake grass, is a vegetable and a well-known herb that is considered an alternative medicine for insect bites, skin rashes, herpes infection, inflammation, and cancer and for health benefits. Current review aims to provide a well-tabulated repository of the phytochemical screening, identification and quantification, and the pharmacological information of C. nutans according to the experimental design and the plant preparation methods which make it outstanding compared to existing reviews. This review has documented valuable data obtained from all accessible library databases and electronic searches. For the first time we analyzed the presence of flavonoids, triterpenoids, steroids, phytosterols, and glycosides in C. nutans based on the results from phytochemical screening which are then further confirmed by conventional phytochemical isolation methods and advanced spectroscopic techniques. Phytochemical quantification further illustrated that C. nutans is a good source of phenolics and flavonoids. Pharmacological studies on C. nutans revealed that its polar extract could be a promising anti-inflammation, antiviral, anticancer, immune and neuromodulating, and plasmid DNA protective agent; that its semipolar extract could be a promising antiviral, anticancer, and wound healing agent; and that its nonpolar extract could be an excellent anticancer agent.